2006
DOI: 10.1021/ja0548945
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Origin of the Dual Fluorescence in Donor−Acceptor Substituted Benzene Derivatives

Abstract: The origin of the dual fluorescence of DMABN (dimethylaminobenzonitrile) and other benzene derivatives is explained by a charge transfer model based on the properties of the benzene anion radical. It is shown that, in general, three low-lying electronically excited states are expected for these molecules, two of which are of charge transfer (CT) character, whereas the third is a locally excited (LE) state. Dual fluorescence may arise from any two of these states, as each has a different geometry at which it at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
117
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(134 citation statements)
references
References 62 publications
(85 reference statements)
16
117
1
Order By: Relevance
“…The twisting model is also supported by using CASSCF optimizations in the excited state and shows that the dipole moment of the CT state reaches a maximum for perpendicular geometries [9]. These calculations, moreover, identify a second coordinate active in reaching the conical intersection to the CT state: this is the Quinoid-Antiquinoid transition (the benzene aromatization coordinate) involving bond length changes within the benzene ring.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…The twisting model is also supported by using CASSCF optimizations in the excited state and shows that the dipole moment of the CT state reaches a maximum for perpendicular geometries [9]. These calculations, moreover, identify a second coordinate active in reaching the conical intersection to the CT state: this is the Quinoid-Antiquinoid transition (the benzene aromatization coordinate) involving bond length changes within the benzene ring.…”
Section: Introductionmentioning
confidence: 67%
“…The latter model corresponds to a large amplitude rearrangement which should strongly depend on viscosity, former does not involve large amplitude changes and therefore the reactions kinetics should be little dependent on solvent viscosity. Recent theoretical advances in the understanding of DMABN favour a large amplitude twisting model [7][8][9]. Robb et al [7] insinuate in the title of their publication, that the reaction coordinate does not include the twist.…”
Section: Introductionmentioning
confidence: 99%
“…Theory has not been able to unambiguously determine the fluorescence mechanism, although many electronic structure methods have been employed to probe the critical points of the S 1 potential energy surface in Curchod, et al -DMABN -Page 3 both gas and condensed phases. Electronic structure methods used to examine the details of the emission process have included linear-response time-dependent density functional theory [12][13][14] (LR-TDDFT), single-reference wavefunction methods such as TDHF/CIS, 15 DFT/SCI, 16 CC2, 17 and ADC(2), 18 and multi-reference wavefunction methods such as CASSCF [19][20][21] and CASPT2. [22][23][24][25] Even though a large number of experimental and theoretical data have been generated on the emission properties of DMABN and its chemical derivatives, much less information is available on the early nonadiabatic, i.e., non-Born-Oppenheimer, relaxation pathway following DMABN photoexcitation.…”
Section: Scheme 1 4-(nn-dimethylamino)-benzonitrile (Dmabn)mentioning
confidence: 99%
“…Lengthening the two central CC bonds (C7-C8 and C10-C11) of the benzene ring, the AQ geometry is obtained using the same active space. Cogan et al [47] reported the similar results in the case of the benzene anion radical, and both Q and AQ both have CT character. After inspecting, however, the Q structure is LE nature and the AQ one has ICT property in this work.…”
Section: Properties and Structures Of Ground State Le State And Ict mentioning
confidence: 53%